Conditioning of boron-containing LRW with composite binders - Rozko, Alla; Fedorenko, Yuriy; Guzii, Sergii (Academic journal Industrial Machine Building Civil Engineering, 2025)
Modern management of liquid radioactive waste (LRW) requires mandatory conditioning, which they practically carried out by cementing, most often with Portland cement. As an alternative to cementing, alkaline binders are used, which are chemically more stable, increase strength over time, and do not pollute the atmosphere with CO2. Most often, the basis of such binders is granulated blast furnace slag in combination with alkaline substances. As a development of LRW management, the direction of conditioning with composite binders we formed, which combines Portland cement and blast furnace slag in composition. Composite binders can take into account the positive properties inherent in the constituent components, while the properties will depend both on the physicochemical parameters and on the conditions under which the LRW is conditioned. The work shows that boron-containing LRWs with a pH > 12 and a total salt content of 60.2% can be conditioned with composite binders, with a ratio of granulated blast-furnace ground slag (particle size < 80 μm): PC-500 cement as 1:1 with a compressive strength > 3 MPa at a temperature of 55 - 60C. The amount of LRW (imitate) in the compound can be 35 - 40%. Alkaline substances included in the LRW composition they used as a binder hardening activator, without the addition of additional alkalis and liquid glass. Depending on the types of components involved: Portland cement, blast-furnace slag or composite binder, samples of compounds with a compressive strength of mainly > 10.3 MPa we obtained.